2014
DOI: 10.2485/jhtb.23.389
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Effect of Local Administration of Fluvastatin using a Fluvastatin-gelatin Complex in Senile Osteoporosis Model Rat

Abstract: Statins, inhibitors of 3-hydroxy-2-methyl-glutaryl coenzyme A reductase, were recently reported to promote the differentiation of osteoblasts produced by the stimulation of bone morphogenetic protein-2 (BMP-2). The aim of this study was to investigate the osteogenic effect of a local administration of fluvastatin in senile osteoporosis model rats using a fluvastatin-gelatin complex. The gelatin-hydrogel was put into cylindrical titanium tubes 1.5 mm in diameter and 2.2 mm high. It was then crosslinked by ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The results showed that improved bone healing was recognized in the low-turnover osteoporosis model. Similar results were reported in our previous study showing that the osteogenic effect of fluvastatin was extended by using a fluvastatin-gelatin complex in senile osteoporosis model rats 13) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that improved bone healing was recognized in the low-turnover osteoporosis model. Similar results were reported in our previous study showing that the osteogenic effect of fluvastatin was extended by using a fluvastatin-gelatin complex in senile osteoporosis model rats 13) .…”
Section: Discussionsupporting
confidence: 92%
“…Previous experiments by our group have shown that local administration of fluvastatin, one of the statins, promotes osteogenesis in normal rat bone defect models using a fluvastatin-gelatin complex 11,12) . In our previous study, influence of the local administration of fluvastatin on bone healing was evaluated in a senile osteoporosis model rat 13) .…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier studies, we used a Gel sponge carrying Flu via electrostatic interactions [18][19][20] . The dissolution rate of this Gel sponge is controllable for up to 3 days by thermal crosslinking 20) .…”
Section: Discussionmentioning
confidence: 99%
“…Crosslinking is accomplished using chemicals such as formaldehyde 24) and glutaraldehyde 25) or physical methods such as UV irradiation 26) and heating [18][19][20] . However, it has been reported that with chemical crosslinking, cytotoxicity of residual reactants from the chemical treatment causes issues 24,25,27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation